The effect of incentives and work environment on employee’s loyalty "Tubagus car spa" west java - Rachmawati, Mariana; Maryani, Maryani; Cumarna, Cumarna (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
Human Resources is one of the most important elements that the company continues to run. Although this is not directly related to the company's finances or income, it can indirectly affect the company's performance. The competitive advantage of the company to survive and compete with other companies is of course very dependent on human resources who have good capacity and quality, based on this, the object and purpose of this study is the Influence of Incentives and Work Environment on Employee Loyalty "Tubagus Car Spa" West Java, the results of his research, Obtained for the variable Intensive value t count 8,871 greater than t table which is 5,781 significant. The confidence variable has a positive regression coefficient of 0.222. the value of t count = 7.780 is greater than the t-table which is 5.594, a significance. The confidence variable has a positive regression coefficient of 0.170.